Upaya meningkatkan hasil belajar pendidikan pancasila dan kewarganegaraan melalui model pembelajaran cooperatif learning tipe number head together kelas xi sma negeri 1 palembang - Aisyah Amini; El Faisal , Emil; Maimun, Maimun (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2023)
This research was conducted at SMA Negeri 1 Palembang. The objects of this research were 38 students of class XI IPA 6. The purpose of this research was to determine the effect of the numbered head together (NHT) learning model on the learning outcomes of students in class XI IPA 6 SMA Negeri 1 Palembang with material on strengthening national unity within the framework of the Unitary State of the Republic of Indonesia. The method used in this study was classroom action research (PTK) which was carried out for three learning cycles, each cycle consisting of the stages of planning (Planning), implementation (Action), observation (Observation), and reflection (reflection). The results of this study indicate that there is an effect of applying the Numbered Head Together (NHT) learning model on student learning outcomes. Judging from the initial data obtained by researchers who show learning outcomes for class XI IPA 6 with an average grade of 72, students who complete are 74% and students who do not complete are 26%, the highest score is 79 and the lowest score is 63 from KKM 70. And the final results obtained in the 3rd cycle of learning increased to an average class value of 87, the percentage of students who completed was 100% and the highest student score was 100 and the lowest score was 80.